Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Komitmen Organisasi di Kantor Pertanahan Kota Ternate - Rio Kurniawan; Mawan Marwan (Jurnal Manajemen Sinergi, 2022)
ABSTRACTObjective: The purpose of this study are: (1) Analyzing the influence of Organizational Culture on the Organizational Commitment of Ternate City Land Office; (2) Analyzing the influence of Work Motivation on the Organizational Commitment of Ternate City Land Office; and (3) Analyzing the influence of organizational culture and work motivation on the Organizational Commitment of Ternate City Land Office. Methodology: The test equipment used is multiple regression analysis using statistical package for social scientists (SPSS) as a statistical test tool. The number of samples is 42 employees. Finding: H1, H2, and H3 are accepted at the 5% confidence level.Conclusion: The results showed that: (1) organizational culture has a positive and significant impact the Organizational Commitment of Ternate City Land Office. It is based on a t value greater than the value of t table, and a smaller significant value of alpha (Î±); (2) work motivation has a positive and significant impact the Organizational Commitment of Ternate City Land Office. It is also based on a t-value greater than the value of t table, and a significantly smaller value of alpha (Î±); and (3) Organizational Culture and work motivation simultaneously have a positive and significant influence the Organizational Commitment of Ternate City Land Office. It is based on the F value count greater than the F table value, and the significant value smaller than alpha (Î±).Â